Enhancing Agricultural Efficiency Through IoT-Based Nutrient Control And Monitoring System For Horticultural Plants - Adimas Ketut Nalendra; Heri Priya Waspada (Universitas PGRI Kanjuruhan Malang, 2025)
There is an increasing need for efficient and effective systems to monitor and control the nutrition of horticultural crops using the Internet of Things (IoT). This research aims to develop a system that can monitor and control the nutrition of horticultural crops with high accuracy using IoT-based sensors and actuators. The research method used is Rapid Application Development (RAD), which starts with listening to users to obtain data on problem needs, building systems by making mockups, and rapidly designing devices according to user needs. The developed IoT system was successfully implemented in the natural environment with Android-based software development. The monitoring data from the database shows that this IoT tool works well during cultivation, and there is no time lag in data retrieval. Monitored data includes pH, water temperature, air temperature, EC, and data recording time. IoT tools for nutrient control and monitoring can also help in irrigation and proper maintenance of plant nutrient needs. The developed IoT system can be used as a solution to optimize nutrition in horticultural crops. This system can control and monitor nutrients in plants using parameters such as water temperature, EC, humidity, air temperature, and water temperature measured by sensors. IoT tools for nutrient control and monitoring can also help maintain plant nutrient requirements through proper irrigation. Therefore, the development and implementation of IoT systems on a larger scale is recommended to increase efficiency and effectiveness in agriculture.